Pendampingan Pembuatan Konten dan Pengelolaan Website Desa Kiringan Boyolali - Muhamad Dani Prasetya; Etty Sri Hertini (Universitas Muria Kudus, 2022)
The development of information technology is so rapid, of course it provides benefits to the community, one of which is the use of websites. Desa Kiran in using the website is still not optimal, as a result there is a lack of content published on the website. The existence of these problems assisting content creation and website management is important to be followed up in order to help Admin Staff and Volunteer Workers (TKS). The purpose of providing assistance is to assist Admin and TKS staff in creating content and managing websites. The method used is the application of science and technology in the form of assistance in content creation and website management. The implementation of mentoring is done through lectures, questions and answers, and direct practice. The result of this assistance is that the Admin and TKS staff can create content and manage the website well.